Introduction to the Creative Humanities. - McFarlane, Brandon (University of Toronto Quarterly, 2022)
The creative humanities respond to the creative turn in art, culture, and higher education. In the decades bracketing the millennium, art and culture were instrumentalized to underwrite growth in the creative economy by attracting world-class talent and generating spin-off benefits for hospitality and tourism. Similarly, higher education was retooled to train labour for the creative economy and bring tangible innovations to Canadian communities. These broadscale shifts present pertinent challenges to humanists: we need new theories to critically examine the production, politics, aesthetics, and second-order consequences of culture vis-à-vis the creative economy, and we also need theories and practices that can strategically situate the humanities within neoliberal models for higher education that increasingly prioritize career preparedness, creativity, innovation, and commercialization. Three emergent theories of humanities creativity and innovation – critical creativity, critical making, and meta-creativity – are delineated to showcase how they can be broadly applied to leverage neoliberal discourse to gain access to resources and opportunities while nevertheless championing alternative models grounded in social justice and the social good.